Determinant factors to the dominance of African grasses in two tropical seasonally dry ecosystems - Xavier, Rafael de Oliveira (2015)
While grasses have a large ecological and economical relevance all over the world, they also may be aggressive invaders. Many African grasses are invaders in other Neotropical seasonally dry ecosystems. Positive response to disturbance and superior competitive ability had been associated with this success, but other species attributes and community features are expected to be important. Here we compare the effect of abiotic stress in the dominance of exotic over native grasses between a reserve of cerrado in the Southeast Brazil and in seasonally dry and early sucessional sites in the Hawai’i Island. Because of the low richness of native grasses in Hawai’i, mostly caused by geographical isolation and short evolutionary history, stressful sites should be more susceptible to invasion there than in the cerrado. We sampled the abundance and performance of these species in multiple sites in both ecosystems, where we also measured major abiotic variables that could cause plant stress. Moreover, we followed the reproductive phenology of species in the cerrado for two years. We estimated the effect of environmental heterogeneity on occurrence and performance of grasses with Chi-square tests and Generalized Additive Mixed Models, and described and compared the phenology of grasses with circular analysis and Pianka’s niche overlap coefficient. In addition to water and disturbance regime, local variation in soil availability and canopy cover were important in Hawaii and in the cerrado, respectively. In both sites exotic grasses were either species that perform very well in a small range of conditions (Urochloa decumbens in the cerrado, and Schyzachyrium condensatum and Hypaerrhaenia rufa in Hawaii), or more generalist species tolerant to intermediate stress (Melinis minutiflora and Melinis repens). Phenological plasticity in U. decumbens and in lesser extent M. minutiflora may contribute with their success in the cerrado, especially because native grasses had high phenological overlap with each other and 1 with two African grasses, and were weakly responsive to environmental variation. While lower rainfall and elevation and newer soils in Hawai’i limited the occurrence of M. minutiflora, they favored M. repens and a native grass. One stress tolerant exotic grass (Andropogon virginicus) was favored in wetter and undisturbed sites with young soils. In contrast, the grasses from cerrado were highly tolerant (Andropogon bicornis), intolerant (T. leiostachya) or generalist species (Loudetipsis chrisothrix) across the gradient of soil waterlogging, but in general were less affected by higher canopy cover than African grasses. Fire could indirectly favor African grasses in both ecosystems, either by increasing N soil content or decreasing canopy cover. Our findings highlight the superior performance of African grasses in mesic condition, but suggest that plastic species as M. minutiflora could succeed at intermediate levels of abiotic stress, especially in Hawai’i. Further studies should address physiological mechanisms of African versus native grasses under stress, and compare ecological and genetic attributes of African grasses in introduced sites and in the native range. Climatic change may favor or constrain different African grasses depending on the region, but the current scenarios of increasing global mean temperatures and spread of arid zones should favor these species. Local predictive models could help to prevent further spread of these species, altogether with fire avoidance and suppression of early invasions.